Biomechanic and Energetic Effects of a Quasi-Passive Artificial Gastrocnemius on Transtibial Amputee Gait - Michael F. Eilenberg; Ken Endo; Hugh Herr (Journal of Robotics)
State-of-the-art transtibial prostheses provide only ankle joint actuation and thus do not provide the biarticular function of the amputated gastrocnemius muscle. We develop a prosthesis that actuates both knee and ankle joints and then evaluate the incremental effects of this prosthesis as compared to ankle actuation alone. The prosthesis employs a quasi-passive clutched-spring knee orthosis, approximating the largely isometric behavior of the biological gastrocnemius, and utilizes a commercial powered ankle-foot prosthesis for ankle joint functionality. Two participants with unilateral transtibial amputation walk with this prosthesis on an instrumented treadmill, while motion, force, and metabolic data are collected. Data are analyzed to determine differences between the biarticular condition with the activation of the knee orthosis and the monoarticular condition with the orthosis behaving as a free-joint. As hypothesized, the biarticular system is shown to reduce both affected-side knee and hip moment impulse and positive mechanical work in both participants during the late stance knee flexion phase of walking, compared to the monoarticular condition. The metabolic cost of walking is also reduced for both participants. These very preliminary results suggest that biarticular functionality may provide benefits beyond even those of the most advanced monoarticular prostheses.